Profil Peninggalan Situs Sejarah Desa Sapit sebagai Bukti Identitas Peradaban Lombok - Jannata, Jannata; Supiarmo, M. Gunawan; Harmonika, Sri; Amrina, Lisa; Alpionita, Resi; Hidayat, Asbur (Universitas Hamzanwadi, 2022)
Sapit is a village rich in natural resources and the hospitality of its people. This village also has cultural diversity, not only in the form of social norms, art, ideas, or inspiration but also in the legacy of letters. The purpose of this study is to describe the profile of the historical site heritage of Sapit village as evidence of the identity of the Lombok civilization. This type of research uses descriptive and qualitative methods to reveal the profile of the historical site heritage of Sapit village as evidence of the identity of the civilization of the Lombok people. The study related to the profile of the historical site heritage of Sapit village was carried out through the data collection stage by conducting observations, data analysis stages, and data interpretation stages. The results show that Sapit village has a wealth of historical sites in the form of Sapit inscriptions, Langgar Pusaka, ancient Qur'an, kentongan, kepeng tepong, and the statue of Dewi Sri. These relics are clear evidence of the advancement of literacy and civilization of the Lombok people from pre-historic times to historical times.Sapit merupakan desa yang kaya akan sumber daya alam, dan keramahtamahan masyarakatnya. Desa ini juga memiliki keanekaragaman budaya, tidak hanya berupa norma sosial, seni, ide atau gagasan, melainkan peninggalan-peningalan aksara. Tujuan penelitian ini adalah mendeskripsikan profil peninggalan situs sejarah desa Sapit sebagai bukti identitas peradaban Lombok. Jenis penelitian ini menggunakan metode kualitatif deskriptif untuk mengungkap profil peninggalan situs sejarah desa Sapit sebagai bukti identitas peradaban masyarakat Lombok. Kajian terkait profil peninggalan situs sejarah desa Sapit dilakukan melalui tahap pengumpulan data dengan melakukan observasi, tahap analisis data, dan tahap interpretasi data. Hasil penelitian menunjukkan bahwa desa Sapit memiliki kekayaan situs sejarah berupa prasasti Sapit, Langgar Pusaka, al-Qur’an kuno, kentongan, kepeng tepong, dan arca Dewi Sri. Peninggalan tersebut menjadi bukti nyata majunya literasi dan peradaban masyarakat Lombok dari zaman pra sejarah sampai zaman sejarah.